Edible Films of Whey and Cassava Starch: Physical, Thermal, and Microstructural Characterization - Andrade Martins, Yasmine Ariadne; Ferreira, Samuel Viana; Silva, Nayane Matias; Sandre, Marcella Fernandes Borges; Oliveira Filho, Josemar Goncalves Oliveira [UNESP]; Leao, Paulo Victor Toledo; Leao, Karen Martins; Nicolau, Edmar Soares; Placido, Geovana Rocha; Egea, Mariana Buranelo; Silva, Marco Antonio Pereira da (Mdpi, 2020)
The present work aimed to obtain and characterize edible films produced with liquid whey and cassava starch. The films were produced with different proportions of whey (63.75-67.50%) and cassava starch (7.50-11.25%) and characterized in relation to physical, thermal, and microstructural properties. The films showed reduced solubility with increasing concentrations of cassava starch, and those with the highest proportions of whey were more stable to thermal decomposition. The increase in concentration of cassava starch altered the microstructure of the films, making them more irregular and with an accumulation of matter. The production of biodegradable polymer blend films is an important step in the development of films for use in packaging, with the formulation of 67.50/7.50% whey/cassava starch being the best film for continued future work.
Keywords: coproduct; thermal degradation; reuse